Kebijakan Delik Penghinaan Presiden Dan Wakil Presiden Dalam Prespektif Hukum Pidana Dalam Kuhp Baru - Ntaki, Fendi Setiawan (Institut Agama Islam Negeri Ponorogo, 2024)
That the debate on the inclusion of the crime of Insulting the President in the New Criminal Code can be said to be a discussion that has attracted quite a lot of public attention, on the one hand, academics who are observers of Human Rights assume that the inclusion of the crime of Insulting the President in the New Criminal Code will violate freedom of expression, and in the Criminal Perspective the Article on Insulting the President must be maintained. that this study aims to determine How the Unlawful Acts of the Crime of Insulting the President and Vice President are in the Perspective of Criminal Law This study uses a normative normative legal approach, which means that the research is carried out by looking at library materials (secondary data) or library legal research. In addition, the analytical descriptive method will be used. The results of this study explain that there are three important notes related to the offense of insult regulated in the New Criminal Code, especially the Article on Insults to the President and Vice President. First, this offense is very subjective, meaning that the assessment of insults is very dependent on the person or party whose good name is attacked. Therefore, insults are complaint offenses that can only be processed by the police if there is a complaint from the person or party who feels insulted. Second, insults are dissemination offenses, meaning that the substance that contains and insults must be disseminated to the public and displayed in public. Third, people who commit defamation by accusing something that is considered insulting to someone or another party must be given the opportunity to prove the accusation. Reports made by the president and vice president are only permitted in accordance with the three articles above because they violate the law and the rights of others.